Multi-material and strength-oriented microstructural topology optimization applied to discrete phase and functionally graded materials - Conde, Fábio M. (2022)
The authors wish also to thank Professor Krister Svanberg (Royal Institute of Technology, Stockholm, Sweden) for the MMA optimization code. Publisher Copyright: © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.